2021
DOI: 10.3390/diagnostics11071219
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for Point-of-Care Fluorescence Imaging for Detection of Wound Bacterial Burden Based on Delphi Consensus

Abstract: Excessive levels of bacteria impede wound healing and can lead to infectious complications. Unfortunately, clinical signs and symptoms of elevated bacterial burden are often unreliable. As a result, point--of--care fluorescence imaging, used to detect critical bacterial burden in wounds, is becoming widely recognized and adopted by clinicians across the globe as an accepted and added component of wound assessment protocol. A Delphi method was employed to establish consensus guidelines describing fluorescence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 41 publications
(62 reference statements)
2
35
0
Order By: Relevance
“…This is consistent with prior reports in which (a) fluorescence information aided wound bed preparation in >85% of wounds, 16 , 23 (b) wound bed preparation aided by fluorescence information was associated with an increase in 12‐week healing rate and 33% decrease in antibiotic prescribing, 30 and is in line with recently published consensus guidelines. 26 In the current study, there were several instances where persistence of red fluorescence signals after these traditional strategies were used indicated that they were insufficient. Together with the irregular pattern of fluorescence extending outside the wound region that suggested cellulitis, this supported the decision to immediately initiate oral antibiotics.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…This is consistent with prior reports in which (a) fluorescence information aided wound bed preparation in >85% of wounds, 16 , 23 (b) wound bed preparation aided by fluorescence information was associated with an increase in 12‐week healing rate and 33% decrease in antibiotic prescribing, 30 and is in line with recently published consensus guidelines. 26 In the current study, there were several instances where persistence of red fluorescence signals after these traditional strategies were used indicated that they were insufficient. Together with the irregular pattern of fluorescence extending outside the wound region that suggested cellulitis, this supported the decision to immediately initiate oral antibiotics.…”
Section: Discussionmentioning
confidence: 66%
“…A fluorescence scan was performed based on medical necessity to aid knowledge of bacteria location at levels requiring treatment, as previously described by Oropallo et al 26 Briefly, these criteria included presence of comorbidities (eg, history of wound infection, non‐healing wounds), presence of clinical signs and symptoms of infection (eg, erythema), indication of bacteria on previous fluorescence scan, or as part of baseline wound assessment. After capturing a fluorescence scan, images were reviewed to identify patterns of fluorescence indicative of bacteria at loads >10 4 CFU/g.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations